Adherence to treatment and anticoagulation control in vitamin K antagonists-treated patients: an administrative databases analysis in a large Italian population - Degli Esposti, Luca; Sangiorgi, Diego; Di Pasquale, Giuseppe; Gensini, Gian Franco; Iori, Ido; Buda, Stefano; Degli Esposti, Ezio (Farmeconomia. Health economics and therapeutic pathways, 2011)
Oral anticoagulant therapy is essential for the treatment and prevention of many thromboembolic disorders. The aim of the present study is to evaluate the level of anticoagulation intensity in patients treated with vitamin K antagonists (VKAs) in a clinical practice setting and to explore the relationship between anticoagulation intensity and adherence to VKA treatment. We conducted a retrospective cohort study using the administrative databases of three Italian Local Health Units. Patients were enrolled if they had filled at least one prescription for VKAs (ATC code B01AA) between January 1st, 2007 and June 30th, 2008. In the same period all determinations of the international normalised ratio (INR) were collected. The parameters evaluated were anticoagulation control and adherence to VKA treatment. The survey showed that only 47.9% and 56.3% of INR determinations, in VKA naïve and established patients respectively, were into the recommended range (2.0-3.0). Moreover, the percentage of INR determination below the recommended range was higher than the percentage of INR determination above the recommended range for both naïve and established patients. Moreover, adherence to VKA treatment was poor both in naïve and established patients and, consequently, anticoagulation control is poor. Also in patients with the highest adherence to VKA treatment, only about 60% of INR determinations were into the recommended range. Our findings evidence that the anticoagulation control in clinical practice settings is still unsatisfactory and it is necessary to evaluate interventions to increase the amount of time at which patients’ INR are within the recommended range.